Physical activity and the risk of non‐Hodgkin lymphoma subtypes: A pooled analysis. Issue 3 (8th September 2022) - Boyle, Terry; Kleinstern, Geffen; Bracci, Paige M.; Cerhan, James R.; Benavente, Yolanda; Casabonne, Delphine; Chiu, Brian C.‐H.; Habermann, Thomas M.; Holly, Elizabeth A.; Liebow, Mark; Norman, Aaron; Paltiel, Ora; et al.
Abstract: Non‐Hodgkin lymphoma (NHL) is composed of a heterogeneous collection of subtypes with considerable differences in genetics, biology and aetiology. Studies to date on physical activity and NHL risk have not had sufficient sample size to evaluate whether associations differ by subtype. We pooled data from nine case‐control studies to examine the association between moderate‐to‐vigorous intensity physical activity (MVPA) and risk of NHL overall and by subtype (diffuse large B‐cell lymphoma, follicular lymphoma, chronic lymphocytic leukaemia/small lymphocytic lymphoma, marginal zone lymphoma and mature T‐cell lymphoma). A total of 5653 cases and 9115 controls were included in the pooled analysis. Physical activity was harmonised across nine studies and modelled as study‐specific tertiles. Multinomial logistic regression was used to estimate the association between physical activity and NHL, adjusting for confounders. The overall odds of NHL was 13% lower among participants in the most active tertile of MVPA compared to the least active tertile (adjusted odds ratio = 0.87, 95% CI = 0.80, 0.95). Similar decreases were observed across NHL subtypes. In summary, in this pooled analysis of case‐control studies, physical activity was associated with a modest risk reduction for each NHL subtype examined and with overall NHL. Abstract : What's new? Studies of the relationship between physical activity and non‐Hodgkin lymphoma (NHL) have not had the statistical power to address NHL's many subtypes. Here, the authors pooled data from nine studies to look for differential associations between activity and five NHL subtypes: diffuse large B‐cell lymphoma, follicular lymphoma, chronic lymphocytic leukaemia/small lymphocytic lymphoma, marginal zone lymphoma and mature T‐cell lymphoma. The most active study participants had a 13% reduction in overall risk of NHL, and similar reductions were seen for all five subtypes.